Modelling the distribution of microplastics released by wastewater treatment plants in Ria de Vigo (NW Iberian Peninsula). (May 2021) - Sousa, Magda C.; deCastro, Maite; Gago, Jesús; Ribeiro, Américo S.; Des, Marisela; Gómez-Gesteira, José L.; Dias, João M.; Gomez-Gesteira, Moncho
Abstract: The accumulation of plastic waste in estuaries is growing due to the increase in their use in daily life and their inadequate treatment on wastewater plants (WWTPs). Hydrodynamic and particle-tracking models were validated and used to improve the knowledge about the distribution and concentration of microplastics released by WWTPs in the Ria de Vigo. Results showed that the Vigo WWTP is the main driver of microplastics to the Ria de Vigo. Besides, 21% of the released microplastics reach the adjacent ocean, 24% remain anchored around the Cies Islands, and a negligible percentage reaches the upper estuary when the emission occurs under ebb on spring tide conditions. A negligible number of released microplastics is exported to the nearby ocean when the emission occurs under neap tide conditions. This research can provide a useful tool to support the identification of monitoring processes and debris removal. Highlights: Delft3D model successfully detected critical zones for microplastics pollution. Wastewater treatment plants are the main source of microplastics in the Ria de Vigo. The microplastics distribution is strongly depend on the tidal stage in Ria de Vigo. Ria de Vigo exports a large quantity of microplastics to the adjacent ocean.